Identifying and selecting socio-technical innovations for women’s empowerment and resilience: A framework for conducting situation analysis - Gartaula, Hom Nath; Nchanji, Eileen Bogweh; Mukhopadhyay, Prama; Molla, Dessalegn; Lutomia, Cosmas Kweyu; Chadha, Deepali; Puskur, Ranjitha; Mpedza, Everisto (International Rice Research Institute, 2023)
Accelerating technology adoption in an equitable and sustainable manner requires a deep understanding of external and internal drivers, social and gender norms, as well as institutional, policy, and regulatory contexts. The complexity of these contexts calls for an approach that involves multistakeholder collaboration and engagement of local communities in the process of codesigning sociotechnical innovation bundles (STIBs). As part of CGIAR’s initiative on gender equality, we are piloting STIBs in selected learning labs in Africa and Asia, and co-developing relevant methods and tools for identifying, prioritizing, and co-designing STIBs. In this session, we present a framework that will guide the process for conducting situation analysis, the process of identifying the entry points for designing and implementing the context-specific and genderresponsive STIBs in a participatory manner with the farmers and other relevant stakeholders. The specific objectives of this framework are: (1) to assist research and development actors who are interested in using STIBs in their programs in designing and conducting situation analysis to understand the local context regarding the social and technical innovations, the sociocultural, economic, ecological/ climatic, and political environments; and (2) to provide general principles, methods and tools that can be applied to conduct situation analysis and present results. In this session, we will share the framework we have developed for conducting situation analysis to identify and select social and technical innovations as entry points for co-designing STIBs in a participatory manner, using tailored tools, techniques and protocols for data collection, analysis, and engaging stakeholders in the process.